Предмет: Алгебра,
автор: kolyadova2001
(х-3)*(х+4)-2*(3х-2)=(Х-4)^2
Ответы
Автор ответа:
0
(х-3)*(х+4)-2*(3х-2)=(Х-4)^2
x^2 - 3x + 4x - 12 -6x +4 = x^2 - 8x + 16
x^2 -5x - 8 -x^2 + 8x - 16 = 0
3x = 24
x=8
x^2 -5x - 8 -x^2 + 8x - 16 = 0
3x = 24
x=8
Автор ответа:
0
X'2+4x-3x-12-6x+4=x'2-8x+16
4x-3x-12-6x+4+8x-16=0
3x-24=0
3x=24
X=8
Похожие вопросы
Предмет: Математика,
автор: slimashuroff
Предмет: Математика,
автор: Аноним
Предмет: Биология,
автор: kizupal2005
Предмет: Литература,
автор: altsagirowa